Sosialisasi Dan Edukasi Implementasi Jaringan Komputer Di Era Industri 4.0 - Erwin Dhaniswara; Darmanto; Agus Prayitno; Robby Kurniawan Budhi (CV. Multi Kreasi Media, 2024)
The implementation of computer networks in the industrial era 4.0 has become important for increasing productivity and efficiency in various sectors. However, there are still many people who do not understand this technology. Therefore, this community service activity aims to increase people's awareness and ability to use computer networks. This activity was carried out by providing education and socialization to the community through online and offline tutoring. The results of the activity show that the community has increased their knowledge and skills in using computer networks. This activity also helps increase public awareness of the importance of technology in the industrial era 4.0.